Comparing Sensitivity to Facial Asymmetry and Facial Identity. (September 2013) - Anderson, Nicole D.; Gleddie, Chris
Bilateral symmetry is a facial feature that plays an important role in the aesthetic judgments of faces. The extent to which symmetry contributes to the identification of faces is less clear. We investigated the relationship between facial asymmetry and identity using synthetic face stimuli where the geometric identity of the face can be precisely controlled. Thresholds for all observers were 2 times lower for discriminating facial asymmetry than they were for discriminating facial identity. The advantage for discriminating asymmetrical forms was not observed using nonface shape stimuli, suggesting this advantage is face-specific. Moreover, asymmetry thresholds were not affected when faces were either inverted or constructed about a nonmean face. These results, taken together, suggest that facial asymmetry is a characteristic that we are exquisitely sensitive to, and that may not contribute to face identification. This conclusion is consistent with neuroimaging evidence that suggests that face symmetry and face identity are processed by different neural mechanisms.